Effect of Oxidative Sardin Fish Oil for Food Utilization - Pitria Andriyani; Tati Nurhayati; Sugeng Heri Suseno (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Sardine is an economic fish industry product in Indonesia. Sardin fish oil of fish meal by-product can be processed into ethyl ester as a food grade product. The purpose of this study were to determine the chemical and physical the best ethyl ester of Semirefined and refined oil from sardine fish meal by-products. Results showed that heavy metals detected was cadmium (Cd) value, i.e. 0.02 ppm. SFA content of crude oil sardines was 29.39% with palmitic acid (16.24%) as the predominant fatty acids. The MUFA content amounted to 14.87% with palmitic acid as the predominant fatty acid (5.76%). The PUFA content were 35.47% with DHA (17.07%) as the predominant fatty acid, while EPA amounted to 13.82%. Semirefined oil  transformed into Semirefined ethyl ester oil was the best on oxidative and physical parameters. Oxidation process produced Semirefined ethyl ester with 1.50±0.00 mEq/kg peroxide value (PV), 0.90±0.15% fattyacids (% FFA), 5.46±0.32 mEq/kg Anisidin p-value (p-AV), 8.46±0.32 mEq/kg oxidation (TOTOKS), 62.15±0.27%T viscosity and and 5.65±0,26 cP clarity.